Pelatihan AutoCAD 3D Secara Online untuk Masyarakat Terdampak Covid-19 - Yoyok Setyo Hadiwidodo; Nur Syahroni; Handayanu; Imam Rochani; Herman Pratikno; Madi Madi (Jurnal Pengabdian Pada Masyarakat, 2022)
The Covid-19 pandemic has had an impact on society, especially in the field of education. Various educational activities are carried out online, so the Service Team holds online AutoCAD 3D training activities to add insight into education and technical design for communities affected by Covid-19. The stages of the program that have been implemented are, the first stage of pre-training which consists of an online survey to communities affected by COVID-19, the design of the AutoCAD 3D training module, and preparation of making online media such as websites, Instagram, and YouTube. The second stage is training which consists of registration of affected communities, online media publications, and online training using online media meetings that are integrated with websites, Instagram, and YouTube. The third stage is post-training in the form of an evaluation to analyze the satisfaction of people who have attended AutoCAD 3D Online training. The results of the analysis of community satisfaction with the facilitators, facilities, presenters, and materials stated that they were 100% very satisfied and satisfied. In addition, the training was also 100% running as expected based on the results of the participant's evaluation.